The Effects of Monetary Policy on Bank Lending and Economic Performance in Nigeria: Array - Olofinlade, Samuel Oluwapelumi; Oloyede, John Adebayo; Oke, Michael Ojo (Acta Universitatis Danubius. Œconomica, 2020)
The study investigated the effects of monetary policy on bank lending and economic performance in Nigeria for the period of 35 years which covered 1984 to 2018. The study addressed broad money supply, monetary policy rate, prime lending rate and inflation rate as monetary policy indicators while real gross domestic product was regressed as economic performance. The data were gathered from Nigeria Central Bank Statistical Bulletin and National Bureau of Statistics. The study employed two models to analyse the effect of monetary policy on bank lending and economic performance respectively by applying the estimation techniques of Augmented Dickey Fuller (ADF) stationarity test and regression analysis. Evidence from model one positioned that money supply and inflation rate have significant influence on bank lending while and monetary policy rate had insignificant influence on bank lending. The second model discovered that money supply has significant influence on economic performance whereas other variables of prime lending rate, monetary policy rate and inflation rate have negative and insignificant effect on economic performance under the study period. However, the study concluded that monetary policy positively and significantly influenced economic performance in Nigeria. It was therefore recommended that Nigeria’s banks should align to government vision of price stability, as well as facilitating the regulatory and supervisory frameworks to secure a strong financial sector for efficient intermediation.